2011
DOI: 10.21608/eajbse.2011.16454
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito breeding sources in Qalyubiya Governorate, Egypt

Abstract: Water collections which may provide breeding habitats for mosquitoes in Qalyubiya Governorate were surveyed throughout the period from April 2009 to March 2011. Mosquito larvae were collected on monthly basis from 14 different breeding places in eight villages. A total of 1800 from 2821 sites (63.8%) were found positive for mosquitoes, including 312 canals, 271 pools, 191 unused wells, 166 rice fields, 142 irrigation channels, 130 ponds, 128 drainages, 115 catch basins, 85 irrigation basins, 82 ditches, 70 swa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 11 publications
2
9
1
Order By: Relevance
“…In contrast with our research, no significant relationship was found between the abundance of the genera Anopheles , Culex and Aedes (formerly Ochlerotatus ) with physicochemical and microbial parameters in Qom Province (central) and Bashagard district, southern Iran [ 19 , 21 ] and Egypt [ 7 ].…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…In contrast with our research, no significant relationship was found between the abundance of the genera Anopheles , Culex and Aedes (formerly Ochlerotatus ) with physicochemical and microbial parameters in Qom Province (central) and Bashagard district, southern Iran [ 19 , 21 ] and Egypt [ 7 ].…”
Section: Discussioncontrasting
confidence: 92%
“…As discussed, some of the data presented in others studies are in agreement [ 1 , 4 , 7 , 9 ] and some in contradiction [ 21 ] with the results of the present study which could be due to biological characteristics of different species that show different levels of tolerance to physicochemical factors.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Observed few anopheles species abundance to dissolved oxygen. Ibrahim AA,El-Monairy OM, El-Sayed, (2011).found that the temperature ,ammonia,and nitrogen are the best predictor for larval density. However no correlation was found between larval density, PH, and dissolved oxygen.…”
Section: Samplementioning
confidence: 99%